PEMERINGKATAN MAKNA MEMBAWA DALAM BAHASA BONAI DIALEK ULAKPATIAN - Zainal Abidin (Madah: Jurnal Bahasa dan Sastra, 2017)
The study on The Categorizing Meaning of “Membawa” in Bonai Language of Ulakpatian Dialect aims at describing words that indicate “membawa” (bring) in many ways in Bonai Language of Ulakpatian Dialect (BLUD). This study is a descriptive qualitative method by analyzing the word meaning components of ‘membawa’ (bring) in BLUD. Primary data in this research are speech data or oral data collected by applying survey method. The data were collected using the conversation method and the listening method by applying some techniques, such as the stimulation and response technique, note taking technique, and recording technique. The research findings reveal that there are fifteen words in BLUD that express 'membawa' namely angket bahamo, bobat, gana, ganit, gopok, horuk, kopag, kopik, moambin, moamit, mujug, munak, nyinyik, nyulag, and sandag. By analyzing the meaning component, the fifteen words can be defined based on the genus proximus and its deferencia specifica.